A composite graphene aerogel for real-time degradation of low-concentration ozone: The synergetic effect of defects. Issue 3 (June 2022) - Xu, Ang; Liu, Pei; Chen, Hongyu; Long, Deng; Lu, Miao; Chen, Xinyi
Abstract: A graphene and manganese oxide composite aerogel has been developed for real-time degradation of low concentrated ozone. Being a widely studied catalyst for ozone degradation, manganese oxide is loaded on graphene aerogel via a one-step method to form a freestanding composite aerogel for ozone degradation. A dynamic degradation percentage over 90% at 0.15 lpm with the initial ozone concentration below 100 ppm can be obtained. The nucleation of manganese oxide as well as the uniformity of the composite aerogels have been found very sensitive to the precursory pH value, which would further influence the performance on ozone degradation. The posting thermal treatment has been applied to adjust the chemical components of the composite aerogels, which has inferred that the synergetic and compensating effect of various defects including structural disorder and functional groups, as well as the components of manganese oxide should hold the responsibility for optimizing the performance on ozone degradation. Graphical Abstract: ga1 Highlights: A composite aerogel based on graphene and manganese oxide has been built for ozone degradation. A dynamic degradation percentage over 90% at 0.15 lpm with the initial ozone concentration around 100 ppm can be obtained. Both graphene and manganese oxide would contribute to the ozone degradation due to a synergetic and compensating effect.